Representasi Makna Dan Pesan Dalam Lirik Lagu “Sebuah Tarian Yang Tak Kunjung Selesai” Oleh Nadin Amizah Menggunakan Pendekatan Semiotik - Siti Yulia Putri Pratiwi (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
This research is motivated by the rise of Nadin Amizah's songs which are difficult for listeners to understand, especially teenagers. Meanwhile, a song is a line of words combined with music and has a meaning or message to be conveyed to listeners. The problem discussed is the meaning and message in the lyrics of the song "A Dance that Never Ends" by Nadin Amizah using a semiotic approach. The purpose of this study is to find out the meaning and message in the lyrics of the song. The benefit of research is that listeners better understand the goals and intentions contained in the song. The research method used in this study uses descriptive qualitative methods. Meanwhile, to analyze the lyrics of the song using the semiotic approach of Ferdinand De Saussure. The result of the research which becomes the signifier is the lyrics of the song "A Dance that Never Ends" by Nadin Amizah, while the signified is the result of an analysis of the meaning of the lyrics. Based on the results of the analysis, the meaning of the lyrics of the song tells about disappointment, including; 1) don't force someone who really wants to leave our life, 2) someone won't be in our life long, and 3). let someone go without having to prevent. Meanwhile, the messages in this song include; 1) must be sincere if someone leaves, and 2) always be grateful for someone's presence in our lives